Delabelling multiple antibiotic allergy: Practical issues - Li, Philip Hei; Thong, Bernard Yu-Hor (Frontiers in Allergy, 2023)
With the growing incidence of multi-drug resistant organisms, delabelling incorrect antibiotic allergies has become an integral part of antimicrobial stewardship worldwide. For example, around 90% of penicillin allergy labels are found to be inaccurate following a full allergy work-up, which deprive patients the use of effective first-line penicillin antibiotics and increase the risk of antimicrobial resistance with the use of other extended spectrum non-penicillin antimicrobials. Significant numbers of adult and paediatric patients over time are labelled with multiple penicillin and non-penicillin antibiotic allergies often during inappropriate antimicrobial use, resulting in a label of “multiple antibiotic allergy”. In contrast to delabelling penicillin allergy where oral direct provocation tests can be used for low-risk, mild reactions, and sensitivity/specificity/positive and negative predictive values of skin tests have been demonstrated, diagnostic tests for multiple antibiotic allergy often require the use of a combination of in-vivo and in-vitro tests across different antimicrobial classes for evaluation. Shared decision making with patients and informed consent are also needed when prioritising which drugs to delabel first, balancing the risks, benefits of testing vs. interim use of alternative antibiotics. Similar to delabelling penicillin allergy, the cost-effectiveness of delabelling multiple drug allergies is unknown.